Chitin and Chitosan preparation from Malaysian Black Soldier Fly biomass: a preliminary study - Mohd Hayati, Mohamad Fayyadh; Ab Rahman, Mohd Hafizuddin; Zulkifli, Nur Saadah; Ruslan, Fatin Shazwani; Darnis, Deny Susanti; Mohd Omar, Suhaila (Trans Tech Publications Ltd, Switzerland, 2022)
Chitin, as well as its deacetylated variant chitosan, has a wide range of applications in biomedical, agricultural, environmental and food industries. Currently, chitin is commercially produced from crustacean shells rather than fungal or insect sources. In this study, chitin from different lifecycle phases of the black soldier fly (Hermetia illucens) (BSF) was extracted and deacetylated into chitosan. Both BSF chitin and chitosan were further subjected to FTIR analysis. The chitin extraction yield % was obtained according to the following order: cocoon>larvae>prepupae. On the other hand, the yield of chemical deacetylation of chitin into chitosan showed a different trend: larvae>prepupae>cocoon. All samples have a deacetylation degree (DD) of more than 90 % except for chitosan from prepupae. FTIR profiles indicated all chitin extracted were in the α-form while the deacetylated chitosan matched closely to the commercially available chitosan. Overall, this study indicated that BSF biomass from different lifecycle phases could be a promising alternative resource for industrial chitin and chitosan production.